Reserves for Economic Growth Due to Reduced Damage from Data Leakages - Akramovich, Turdiev Odilzhan (European Journal of Life Safety and Stability (2660-9630), 2022)
The article analyzes the reserves of economic growth as a result of reducing the damage from data leaks, an attempt is made to generalize the main problems in the field of financial security in foreign countries, at the same time, a number of world-class problems are noted in terms of preventing information threats to ensure the financial security of enterprises.